The complete mitochondrial genome of the blue skate Dipturus batis. Issue 3 (2nd July 2020) - Delaval, Aurélien; Schwanck, Tanja; Kopp, Martina Elisabeth Luise; Hoarau, Galice; Jones, Catherine S; Noble, Leslie R
Abstract: The complete mitochondrial genome of the blue skate Dipturus batis is described from shotgun sequencing on an Illumina next-generation sequencing platform. We report a 16, 911 bp long sequence similar in size to other members of the genus, containing 13 protein-coding regions, 22 tRNA genes, 2 rRNA genes, and 2 non-coding areas. Phylogenetic analysis was performed using the complete mitochondrial genomes of 17 related species, placing D. batis within the Rajini tribe of the Rajidae family, consistent with current taxonomy. The new resource adds to a growing database of rajid mitogenomes which will help resolve phylogenetic relationships within the family.